UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI LINGKARAN DENGAN MENERAPKAN DISCOVERY LEARNING - Rubiyati, Rubiyati (Persatuan Guru Republik Indonesia Kota Semarang, 2022)
Based on the background of the problems described above, several problems can be identified as follows: students are less able to master Mathematics learning in class VI even semester of SD Negeri Tlogosari Kulon 03. Of the 40 children only 16 children (40.00%) reached the KKM. The teacher's efforts to improve the ability of learning outcomes in the material